Legal standards of Ukrainian cultural heritage preservation in the context of post - war reconstruction and integration into the EU - Pokhylenko I. S.; Akimov M. O. (Baltija Publishing, 2024)
Cultural heritage is a set of cultural values inherited by the contemporaries from the previous generations which are the essential part of national self-respect and the appropriate representation of the country at the international level. According to international conventions, ratified or signed by Ukraine (theEuropean Convention on the Protection of the Archaeological Heritage, the Convention on the Protection of the Underwater Cultural Heritage, the Convention for the Protection of the Architectural Heritage of Europe, the Convention for the Safeguarding of the Intangible Cultural Heritage, the Council of Europe Framework Convention on the Value of Cultural Heritage for Society), the protection of cultural heritage is an international legal obligation of Ukraine to the world community.The occupation of the Crimea, conflict in the East of Ukraine and the armed aggression of the Russian Federation against Ukraine in February 2022 have created problems related to the abduction, appropriation of cultural values, their illegal export and destruction which require an immediate solution. Legal regulation of protection and repatriation of cultural heritage is ineffective with regard to the protection of cultural values on the occupied territories; therefore the time has come to significantly improve the provisions of current legislation with regard to the existing realities and new challenges. Consequently Ukraine must take all measures to repatriate illegally exported cultural values and to demand the prosecution of those responsible for the deliberate destruction of the objects of cultural heritage.The aim of this article is to outline peculiarities of legal regulation of cultural heritage protection during the Russian-Ukrainian War
Keywords: Russian-Ukrainian War; cultural heritage; European Union; 719:34-021.68(477)